Advertising and promotion: an Islamic perspective - Mokhtar, Aida (2019)
The life of Muslims should be guided by Islam in a holistic manner including in matters of business and promotion. Promotion is an essential part of marketing bringing buyers and sellers together in the marketplace. Without advertising that is a branch of promotion, customers would not be in the know of new products or be reminded of them. The creation of television advertising messages require closer scrutiny in view of its Shari’ah compliance. Much of the previous literature has been on advertising and cultural values and there appears to be a dearth of studies identifying Shari’ah principles for examining advertisements from the Islamic perspective. This paper aims to provide a definition of Shari’ah and the principles of a code of conduct based on the Maqasid Shari’ah for guiding the production of television advertisements of halal products. Islam is divided into Aqidah (belief), Shari’ah (Islamic law) and Akhlaq (etiquette). Shari’ah is further divided into Ibadah (worship of Allah) that focuses on the relationship and interaction between human beings and their Creator and Muamalah (civil and commercial acts) that focuses on the relationship and interaction among human beings. Television advertising is related to Muamalah in Islam.